Clinical Utility of a Risk‐Adapted Protocol for the Evaluation of Coronary Artery Disease in Liver Transplant Recipients. Issue 8 (25th June 2019) - Romero‐Cristóbal, Mario; Mombiela, Teresa; Caballero, Aranzazu; Clemente, Ana; Fernández‐Yunquera, Ainhoa; Diaz‐Fontenla, Fernando; Rincón, Diego; Ripoll, Cristina; Bermejo, Javier; Catalina, María‐Vega; Matilla, Ana‐María; Ibáñez‐Samaniego, Luis; et al.
Abstract : The prevalence and management of coronary artery disease (CAD) in liver transplantation (LT) candidates are not well characterized. The aims of this study were to evaluate the impact on clinical outcomes of a specifically designed protocol for the management of asymptomatic CAD in LT candidates and to investigate noninvasive risk profiles for obstructive and nonobstructive CAD for 202 LT candidates. Those with high baseline cardiovascular risk (CVR; defined by the presence of classic CVR factors and/or decreased ejection fraction) received coronary angiography and significant arterial stenosis and were treated with percutaneous stents. Patients were followed up after LT until death or coronary event (CE). There were 78 patients who received coronary evaluation (62 direct angiography, 14 computed tomography coronary angiography, and 2 both). Of them, 39 (50%) patients had CAD of any severity, and 6 (7.7%) had significant lesions (5 were amenable to be treated with stents, whereas 1 patient had diffuse lesions which contraindicated the LT). Insulin‐dependent diabetes was the only factor related to CAD of any severity (odds ratio, 3.44; 95% confidence interval [CI], 1.00‐11.97). A total of 69 patients (46 with coronary evaluation) received LT. The incidence of CEs and overall survival after LT were similar between patients with and without coronary evaluation. Furthermore, no differences occurred between these groups in a multivariate competing risk model (subhazard ratio, 0.84; 95% CI, 0.27‐2.61; P = 0.76). In conclusion, the application of an angiographic screening protocol of CAD in a selected high‐risk Mediterranean population is safe and effective. The short‐ and medium‐term incidence rates of CEs and death after LT in this population are similar to that observed in low‐risk patients.